Supramolecular chemistry of liquid-liquid extraction - Pramanik, Sourav; Islam, Abu S. M; Ghosh, Iti; Ghosh, Pradyut (Chemical science (Cambridge), 2024)
Liquid-Liquid Extraction (LLE) is a venerable and widely used method for the separation of a targeted solute between two immiscible liquids. In recent years, this method has gained popularity in the supramolecular chemistry community due to the development of various types of synthetic receptors that effectively and selectively bind specific guests in an aqueous medium through different supramolecular interactions. This has eventually led to the development of state-of-the-art extraction technologies for the removal and purification of anions, cations, ion pairs, and small molecules from one liquid phase to another liquid phase, which is an industrially viable method. The focus of this perspective is to furnish a vivid picture of the current understanding of supramolecular interaction-based LLE chemistry. This will not only help to improve separation technology in the chemical, mining, nuclear waste treatment, and medicinal chemistry sectors but is also useful to address the purity issue of the extractable species, which is otherwise difficult. Thus, up-to-date knowledge on this subject will eventually provide opportunities to develop large-scale waste remediation processes and metallurgy applications that can address important real-life problems. In this perspective we have summarized the current understanding of supramolecular interaction-based liquid-liquid extraction.